Numerical study on the transverse jet flow and mixing characteristics of hydrogen/metal powder fuel in powder fuel scramjet. (15th October 2022) - Ding, Hongming; Zhuo, Changfei; Chen, Xiong; Deng, Hanyu; Li, Maoquan; Sun, Bo; Li, Chunlei
Highlights: The particle disturbance intensifies the Kelvin-Helmholtz instability; The vortex structure is the main factor affecting hydrogen fuel mixing; The mixing efficiency of powder fuel is affected by the initial state; The fuel mixing of the double-hole jet is better than that of the single-hole. Abstract: The powder fuel scramjet is one of the most promising propulsion systems for future hypersonic vehicles. To study the flow mechanism and mixing characteristics of gas-particle two-phase fuel in a supersonic crossflow. In this study, the porosity was introduced into the Navier-Stokes equation, and a program suitable for solving gas-particle two-phase flow in the supersonic flow field was developed. The evolution process of vortex structure, hydrogen/metal powder fuel distribution, jet penetration depth, and mixing efficiency in the single-hole and the double-hole jet flow fields were analyzed. The results show that the particle disturbance reduces the center position of the Mach disk, the height of the barrel shock and jet shear layer, intensifies the Kelvin-Helmholtz instability in the flow field and forms a large number of large-scale coherent structures downstream of the jet. The jet and supersonic crossflow interaction form a large-scale CVP structure for hydrogen fuel. Among them, three pairs of CVP structures (including CVP-B, CVP-C, and CVP-D) appear before and after the downstream of the double-hole jet. CVP-C is the main factor affecting the shape and area of the hydrogen fuel reaction zone. For powder fuel, the penetration depth of fuel is mainly affected by the height of the Mach disk and the shear layer. The higher Mach disk and shear layer position, the greater the velocaity obtained by particles and the higher the penetration kinetic energy. The double-hole injection system has a higher fuel penetration depth and higher mixing efficiency of hydrogen and powder fuel. The mixing efficiency of hydrogen fuel at the outlet of the double-hole jet is 0.728, which is 10% higher than that of the single-hole jet; The mixing efficiency of powder fuel is 0.342, which is 2% higher than that of the single-hole jet. However, the complex flow field structure of the double-hole jet leads to a large total pressure loss, about 0.74% higher than that of the single-hole jet.